Transfer of Technology for Tactical Floating Bridge Local Fabrication - Mohamad Fariz, Mohamed Nasir*; Abdul Rahman, Abd Rahim; Muhammad Fathi, Yusof; Muhammad Izzat Nor, Ma'arof; Girma, Tadesse Chala (INTI International University, 2023)
In this study, the focus was on the study of the transfer of technology that takes place in the Royal Engineer Regiment. The study began with a review of the literature on the transfer of technology that occurs in the Malaysian Armed Forces and the country's defense industry. The study includes the identification of problems, implementation strategies, and methods used to carry out the transfer of technology in the defense industry. Technical studies were conducted to gather information on the concept of construction for tactical floating bridge modules using the case study as well as the direct involvement during handling of the asset. The collection of data on the problem, the next execution of strategies and methods are reviewed and concepts to solve problems, the proposal of implementation strategy and propose methods for local manufacturing of tactical pontoon bridge. The study will be able to create better awareness to the transfer of technology and assist in the defense of the country through the provision of better war equipment and more easily available.